The earth - Butterfield, Moira, 1961-; Bull, Peter, 1960-; Hill, Sandy; Mainline Design (Firm) (New York : Kingfisher Books, 1992)
Examines the volcanoes, rivers, deserts, rain forests, weather, and other facets of our planet.
Includes index.
Keywords: Earth -- Juvenile literature; Earth -- Miscellanea